Effect of Mild Hypothermia after Craniotomy on the Function of Related Organs in Patients with Traumatic Brain Injury - Shu Cai; Zheng Lu (Emergency Medicine International)
Objective. To investigate the effect of mild hypothermia after craniotomy on the function of related organs in patients with traumatic brain injury. Method. A total of 240 patients with craniocerebral injury from January 2017 to December 2020 were retrospectively analyzed. Patients were randomly divided into a control group and an experimental group, with 120 cases in each group. The control group was treated with craniotomy decompression, and the experimental group was treated with early mild hypothermia based on craniotomy decompression. Patients’ venous blood was collected before operation (T0), at the end of operation (T1), 24 h after operation (T2), and 2 weeks after operation (T3) to detect the serum levels of the beta-subunit of S100 protein (S100-β); soluble growth stimulation expressed gene 2 (sST2), neutrophil gelatinase-associated lipocalin (NGAL), and interleukin 6 (IL-6). The prognostic effect was evaluated after 2 weeks of treatment. Results. After mild hypothermia treatment after craniotomy and decompression, the patients’ serum S100-β, sST2, NGAL, and IL-6 levels at different time points were significantly lower than the control group, and the total effective rate was higher than that of the control group. Conclusion. The treatment of mild hypothermia after craniotomy can reduce the related organs function damage indicators and inflammatory stress response, thus improving clinical efficacy and prognosis.